THE INDIVIDUAL LEARNING PROCESS ARISING FROM ERRORS COMMITTED BY MANAGERS IN NEW TECHNOLOGY-BASED FIRMS - Rodrigues, Henrique Geraldo; de Souza Bido, Diógenes (Contextus - Revista Contemporânea de Economia e Gestão, 2019)
The purpose behind this article was to identify and analyse, in the context of technology-based firms, the process by which individual error was addressed and how its occurrence led to learning. Through a basic qualitative research study, nine managers were interviewed from Brazilian-based technology firms. The main results indicate that the situation-problem, in which the effects of errors are manifest, is established upon an important stage for error detection and correction. Also, a procedural path was outlined for individual learning from errors at work, which shows how the stages of error detection and correction articulate with elements that positively influence learning. Such perspectives imply that approaches to the phenomenon should consider that the effectiveness of learning from errors is dependent upon individual involvement in treating the problem.